Grappling with the bomb : Britain's Pacific H-bomb tests - Maclellan, Nic (2017)
Grappling with the Bomb is a history of Britain's 1950s program to test the hydrogen bomb, code name Operation Grapple. In 1957-58, nine atmospheric nuclear tests were held at Malden Island and Christmas Island–today, part of the Pacific nation of Kiribati. Nearly 14,000 troops travelled to the central Pacific for the UK nuclear testing program–many are still living with the health and environmental consequences. Based on archival research and interviews with nuclear survivors, Grappling with the Bomb presents i-Kiribati woman Sui Kiritome, British pacifist Harold Steele, businessman James Burns, Fijian sailor Paul Ah Poy, English volunteers Mary and Billie Burgess and many other witnesses to Britain's nuclear folly.